2021
DOI: 10.1016/j.hroo.2021.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Performance and outcomes of transvenous rotational lead extraction: Results from a prospective, monitored, international clinical study

Abstract: Background Transvenous lead extraction (TLE) plays a critical role in managing patients with cardiovascular implantable electronic devices. Mechanical TLE tools, including rotational sheaths, are used to overcome fibrosis and calcification surrounding leads. Prospective clinical data are limited regarding the safety and effectiveness of use of mechanical TLE devices, especially rotational tools. Objective To prospectively investigate the safety and effectiveness of mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
29
3
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 19 publications
8
29
3
3
Order By: Relevance
“…Recently, single and multicenter studies reported that the second generation of the Evolution system (Evolution RL) has emerged as alternative mechanical TLE tool for extraction of chronically implanted leads. [7][8][9][10][11] The efficacy of the system, equal to that of laser powered sheaths, has led to an increase in its use in clinical practice as a firstline approach in centers with experienced operators when advanced TLE techniques are needed in complex cases and long lead implant duration. The present study not only confirmed and extended previous observations, demonstrating that the Evolution RL system is an effective TLE tool with high success rates, but also reported its use in combined procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, single and multicenter studies reported that the second generation of the Evolution system (Evolution RL) has emerged as alternative mechanical TLE tool for extraction of chronically implanted leads. [7][8][9][10][11] The efficacy of the system, equal to that of laser powered sheaths, has led to an increase in its use in clinical practice as a firstline approach in centers with experienced operators when advanced TLE techniques are needed in complex cases and long lead implant duration. The present study not only confirmed and extended previous observations, demonstrating that the Evolution RL system is an effective TLE tool with high success rates, but also reported its use in combined procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Complete procedural success, per lead, in our study was slightly lower compared with recent multicenter studies, such as the PROMET 10 and the RELEASE studies. 11 This may due to differences in patient populations. Indeed, our study population had higher infection indication for TLE and more passive leads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This current study by Sharma and colleagues 6 compares favorably with these studies and includes clinical follow-up data at 4 weeks. It represents one of the largest international, prospective studies of mechanical TLE.…”
mentioning
confidence: 99%
“…In this issue of Heart Rhythm O 2 , Sharma and colleagues 6 provide an insightful prospective study aimed at understanding the safety and efficacy of the Cook Medical Evolution® RL mechanical rotational TLE device (RELEASE study). Ten medical centers in the United States and Europe were involved, with 230 patients enrolled for a total of 460 leads extracted.…”
mentioning
confidence: 99%